The Efficacy of Protective Nets Against Drosophila suzukii: The Effect of Temperature, Airflow, and Pest Morphology - Antonio J. Álvarez; Rocío M. Oliva; Jaime Martínez-Valderrama (Insects)
Drosophila suzukii is an invasive pest that poses a significant threat to fruit crops worldwide, leading to considerable agricultural losses and economic damage. Unlike chemical control measures against D. suzukii, integrating insect-proof nets within an IPM framework offers a more sustainable solution. This study evaluates the efficacy of nine commercial protective nets against this pest, focusing on determining optimal hole dimensions based on the effects of airflow velocity, temperature, and pest morphometry on net performance. To simulate field conditions in the laboratory, we developed a tubular device divided into three chambers with the tested net placed between the two, incorporating a fan to generate airflow and a thermo-anemometer. Our results confirm that higher air velocities and elevated temperatures reduce net efficacy. Additionally, morphometric analyses of lab-reared flies revealed significant sexual dimorphism and a strong temperature–size relationship, with flies reared at lower temperatures being consistently larger, an aspect that also affects net effectiveness. These findings highlight the importance of considering both abiotic factors and pest morphology when evaluating protective screens, challenging the assumption that exclusion net efficacy remains constant. Some tested nets proved completely effective against SWD, supporting their use as a preventive measure in IPM programs.